Changes in the chemical composition and medicinal effects of black ginseng during processing - Qiu, Ye; Wang, Nengyuan; Yu, Zhe; Guo, Xiao; Yang, Ming (Frontiers in Pharmacology, 2024)
Aim of the Study To study the changes in the chemical composition and medicinal effects of black ginseng during processing. Materials and Methods The contents of ginsenosides Rg1, Re, Rh1, Rb1, 20-(S)-Rg3, 20-(R)-Rg3, and Rg5 were determined using high-performance liquid chromatography (HPLC), and the percentage of rare saponins was calculated. Furthermore, changes in the contents of reducing sugars and amino acids (i.e., Maillard reaction (MR) substrates) were measured to assess the relationship between processing and the MR. Compounds were identified using HPLC-MS and their cleavage patterns were analyzed. Gene co-expression network bioinformatics techniques were applied to identify the pharmacological mechanism of black ginseng. Results The changes in the physicochemical characteristics of black ginseng during processing were determined based on the MR. Rare saponins accumulated during black ginseng processing. In addition, reducing sugars were produced through polysaccharide pyrolysis and the MR; thus, their content initially increased and then decreased. The amino acid content gradually decreased as the number of evaporation steps increased, indicating that both amino acids and reducing sugars acted as substrates for the MR during black ginseng processing. Thirty-one saponins, 18 sugars, and 58 amino acids were identified based on the MS analysis. Transcriptomics results demonstrated that black ginseng can regulate signaling pathways such as the TNF, IL-17, MAPK, and PI3K-Akt pathways. This finding helps us understand the observed proliferation and differentiation of immune-related cells and positively regulated cell adhesion.